Labor market assimilation of recent immigrants in Spain - Catalina Amuedo-Dorantes; Sara de la Rica (Institute for the Study of Labor (IZA), 2006)
This paper provides a preliminary analysis of the employment and occupational assimilation of recent immigrant waves to the Spanish labor market as their residencies lengthen. Using Spanish data from the 2001 Population Census and the 2002 Earnings Structure Survey, we find evidence of immigrant employment and occupational assimilation significantly varying by gender, origin and educational attainment. For instance, EU15 immigrants do not display an employment or occupational gap with respect to natives, whereas immigrants originating from non-EU15, African or Latin American countries do. Yet, among the latter, non-EU15 and Latin American immigrants assimilate employment and occupation-wise, while there is limited evidence of labor market assimilation among African immigrants.
Keywords: J61; 330; immigrant assimilation; employment; occupational attainment and mobility; Spain